Evaluation of Performance of Flux Switching Motor in Segmented Rotor Using Permanent Magnet For Direct Drive - Mbadiwe, Enwelum I.; Sulaiman, Erwan B. (International Journal of Engineering and Technology, 2018)
The torque action provided by combustion engine in conventional vehicles has been boosted by added electric motor, a device which also provide torque, for fuel economy in hybrid electric vehicle. Meanwhile, the complicated nature of combustion engine still poses economic imperatives as petroleum resources are getting depleted. Interestingly, vehicles propelled by electric motor powered by electricity, will completely eliminate combustion engine using fossil oil and also provide clean and reliable vehicles for personal transportation. Since electric motor is a core component, high torque motors are necessary for direct drive application. This papers presents a feasible 24 stator - 10 rotor segments flux switching motor (FSM) using 1 kg weight of PM. FSM is advance form of synchronous machine with double frequency that locates all active materials on the stator only. Permanent magnet (PM) flux source is chosen because it offers loss free excitation without external circuit connection. The JMAGÂ® Studio tool version 14.1 was employed for 2D- FEA design and performance investigation of motor in terms of cogging torque and average torque.Â  Finally, simulation result of proposed motor successfully achieved 352Nm and constant power of 36kW projecting it as viable candidate for high torque necessary for direct drive application.